EFECTS OF MENTHA PIPERITA (L.) EXTRACT MIXED DIETON HEPATIC HISTOLOGICAL ALTERATION AND DISEASE RESISTANCE AGAINST AEROMONAS HYDROPHILA INFECTION IN ROHU (LABEO ROHITA HAM.) - Thuy, Nguyen Thi Thanh (Vietnam Journal of Marine Science and Technology, 2008)
Rohu (Labeo rohita Ham.) fingerlings with average weight of 35 ± 2g were randomly divided into four groups (13 fish/tank in duplicate) viz., the control (fed on normal diet) and three treated groups namely T1, T2 and T3 treatments fed on Mentha piperita (L.) extract mixed diet with varying doses i.e. 10, 20 and 30 ml/100g feed, respectively. After three weeks of treatment, fish from all the groups were sampled (3 fish/tank) for hepatic histological examination. Then, all the fish groups were immunized intraperitoneally (i.p.) with a dose of 106 cells/fish of formalin-killed Aeromonas hydrophila suspension. After two weeks of immunization, all the treatments were challenged (i.p) with a dose of 106 cells/fish of live A. hydrophila suspension. After challenge, all the fish treatments were fed on the same normal diet and observed daily cumulative mortality. Moribund infected fish and survival fish after two weeks of challenge were sampled for histopathological examination. The results indicated that there was no histological alteration in liver tissues of M. piperita (L.) extract treated fish. However, A. hydrophila infected fish showed histopathological alteration such as degenerative hepatocytes and congestion of liver tissues. Disease resistance against A. hydrophila increased in the M. piperita (L.) extract treated groups with the highest in the T3 treated group.